ASPEK HUKUM PEMBENTUKAN PRODUK HUKUM DAERAH DALAM PENANGGULANGAN PANDEMI COVID-19 - Madjid, Mahatir (TADULAKO MASTER LAW JOURNAL, 2025)
The results of the study obtained the conclusion 1). The legal aspects of the formation of regional legal products in overcoming the Covid-19 pandemic can be seen from the Philosophical Aspect, that Pancasila is the source of all sources of state law, so that every content material of laws and regulations related to overcoming the Covid-19 pandemic must be in accordance with the values contained in Pancasila. The Sociological Aspect, that overcoming the Covid-19 pandemic at that time, required quick and precise steps from the central and regional government apparatus, while still ensuring legal certainty to protect the interests of all citizens. As for the Juridical Aspect, that policy regulations and regional legal products that regulate the handling of the Covid-19 pandemic, are recognized for their existence and have binding legal force as long as they are ordered by higher laws and regulations and / or formed based on the legal authority of the forming organs. 2). The function of the Ministerial Instruction as a policy regulation, towards the formation of regional legal products in overcoming the Covid-19 pandemic, is to fill the legal vacuum as the basis for the formation of regional legal products, the implementation of government functions and authorities at the central and regional levels, and provide fair legal protection to every citizen regardless of ethnicity, religion, position, race and group. Hasil penelitian memperoleh kesimpulan 1). Aspek hukum pembentukan produk hukum daerah dalam penanggulangan pandemi Covid-19, dapat ditinjau dari Aspek Filosofis, bahwa Pancasila sebagai sumber dari segala sumber hukum negara, sehingga setiap materi muatan peraturan perundang-undangan terkait penanggulangan pandemi Covid-19 harus bersesuaian dengan nilai-nilai yang terkandung dalam Pancasila. Aspek Sosiologis, bahwa penanggulangan pandemi Covid-19 saat itu, membutuhkan langkah cepat dan tepat dari aparatur pemerintahan pusat dan daerah, dengan tetap menjamin kepastian hukum melindungi kepentingan semua pihak warga negara. Adapun Aspek Yuridis, bahwa peraturan kebijakan dan produk hukum daerah yang mengatur penanggulangan pandemi Covid-19, diakui keberadaan dan mempunyai kekuatan hukum mengikat sepanjang diperintahkan oleh peraturan perundang-undangan yang lebih tinggi dan/atau dibentuk berdasarkan kewenangan sah (legal) organ pembentuknya. 2). Fungsi Instruksi Menteri sebagai peraturan kebijakan, terhadap pembentukan produk hukum daerah dalam penanggulangan pandemi Covid-19, untuk mengisi kekosongan hukum sebagai dasar pembentukan produk hukum daerah, pelaksanaan fungsi dan kewenangan pemerintahan di pusat dan daerah, dan memberikan perlindungan hukum yang adil kepada setiap warga negara tanpa memandang suku, agama, jabatan, ras dan golongannya